The Crescent Moon on the Island of Gods, Traces of Muslim Village Kusamba-Bali - Edited by AAGN Ari Dwipayana; Reviewed by: Farninda Aditya (Al-Albab, 2015)
Who does not know Bali, a beautiful island that fascinates many tourists from around the world, with a religious identity as it is commonly referred to as the Island of Gods. Despite being well-known as the Land of the Hindus, Bali has a Muslim village, where Muslim residents live side by side with the Hindu Balinese. When one recalls the Bali bombing incident in 2002 and 2005 in Kuta, Jimbaran, certainly they will express an opinion on the social and religious tension between these two religious groups. The tragedy has in fact left a change in attitudes i.e. the strengthening of the Balinese identity, which is presented in the book entitled Bulan Sabit di Pulau Dewata: Jejak Kampung Islam Kusamba-Bali (The Crescent Moon on the Island of Gods, Traces of Muslim Village Kusamba-Bali).